(untitled) (Journal of Dhaka Medical College, 2023)
Background: Placenta previa (PP) is defined as placenta implantation in the lower uterine segment with or without overlying the endocervical os. It is a significant cause of severe fetal and maternal morbidity and mortality. Objective: To evaluate the maternal and neonatal outcome of placenta previa lying over the uterine scar due to previous one or two caesarean sections. Material and Methods: This descriptive type of observational study was done in the Department of Obstetrics & Gynaecology, Enam Medical College & Hospital, Savar, Dhaka, from December 2020 to June 2021. All relevant data were collected prospectively in a prescribed form (questionnaire). Data were processed and analysed with the help of the computer program SPSS (Statistical Package for Social Sciences) windows version 25. Results: This study shows the most familiar age group was 26-30 years, which included 46%, and 38% belonged to the 31-35 age group. The average age was 29.93 years. Maximum (54%) number of cases were admitted during the gestational period of 35-38 weeks. It was observed that maternal outcome was profuse intraoperative blood loss (100%), post-partum haemorrhage (26%), transfusion requirement (100%), and post-partum anaemia (28%). In addition, the outcome was fetal distress (36%) and lower Apgar scores at 1 min (24%). Conclusion: This study shows women with placenta previa lying over the uterine scar were more likely to have poorer maternal and neonatal outcomes. To counsel their patients appropriately, healthcare providers should be aware of possible complications of placenta previa lying over the uterine scar. J Dhaka Med Coll. 2022; 31(1) : 56-60